The Scientific Principle of Food Safety in the Agreement on Sanitary and Phytosanitary Measures - Yusuf Adiwibowo (University of Jember, 2020)
Sanitary and Phytosanitary (SPS) is a procedure to protect human, animal, or plant life or health set in Article XX(b) of the General Agreement on Tariffs and Trade (GATT). This Agreement authorizes the government to arrange a policy, but this domestic measure often results in a trade dispute. Therefore, this study enquires to extent measure on the scientific principle in food safety comply with Article XX (b) GATT. In the context, each WTO Member State has two options to show that measures of handling problems related to SPS are based on science, as outlined in Article XX (b) GATT must be measured by the scientific principle. First, actions can be based on international standards so that each member state must adopt the Codex Alimentarius Commission. Second, actions can be based on Scientific Risk Assessment. SPS Agreement recognizes states' right to maintain standards that are more stringent than international standards, or because international standards do not exist. The relevant scientific principle are useful for measurable events with scientific information beforehand so that the existing measures can guide the state's policy. In vice versa, members may temporarily determine sanitary or phytosanitary actions based on available information. KEYWORDS: Scientific Principle, Food Safety, SPS Measures, WTO.